Heat stress during development makes antlion larvae more responsive to vibrational cues. Issue 3 (9th December 2021) - Miler, Krzysztof; Czarnoleski, Marcin
Abstract: We investigated the effects of heat stress on the responsiveness to vibrational cues, our measure of perceptual ability, in Myrmeleon bore antlion larvae (Neuroptera: Myrmeleontidae). We reared these trap-building predatory larvae under 2 heat stress regimes (mild, 30°C, and harsh, 36°C), and after they progressed from one instar stage to another, we tested their perceptual ability in common unchallenging conditions. We hypothesized that exposure to the harsh heat stress regime would impose costs resulting in handicapped vibration responsiveness. We found that the harsh heat stress regime generated more stressful conditions for the larvae, as evidenced by increased mortality and postponed molting, and the loss of body mass among larger larvae. Furthermore, among the individuals who remained alive, those originating from the harsh heat stress regime were characterized by higher vibration responsiveness. Our results suggest 2 not mutually exclusive scenarios. Costly heat stress conditions can sieve out individuals characterized by poor perceptual ability or surviving individuals can attempt to hunt more efficiently to compensate for the physiological imbalance caused by heat stress. Both of these mechanisms fit into the ongoing debate over how adaptation and plasticity contribute to shaping insect communities exposed to heat stress.